Treatment Of Grade II Diabetic Ulcer with Mindi Leaf Hydrogel (Melia Zadarach L) Against Wound Healing Process - Ineke Noviana; Mardiyono Mardiyono; Dwi Ari Murti Widigdo (Universitas STRADA Indonesia, 2021)
Diabetic ulcers are a chronic complication of Diabetes Mellitus. Modern society prefers non pharmacology as a nursing action because it is far from chemicals. Researchers found that mindi leaves with ingredients that can be used as anti-inflammatory, antidiabetic and antibacterial can be used to treat diabetes which is packaged into a hydrogel for the basic ingredient of modern care (modern dressing).To determine the effectiveness of mindi leaf hydrogel on the wound healing process in patients with grade II diabetic ulcers. True experimental design with pre-test post-test with control group design. Data were collected by taking 40 respondents through stratified random sampling and the hypothesis was tested by using the General Linear Model effectiveness test.Mindi leaf hydrogel significantly accelerated the healing process of grade II ulcers with a value of p=0.000.Treatment of diabetic ulcers with mindi leaf hydrogel is effective in accelerating the wound healing process